2005
DOI: 10.1007/s10461-005-1684-1
|View full text |Cite
|
Sign up to set email alerts
|

Patient?Clinician Relationships and Treatment System Effects on HIV Medication Adherence

Abstract: The study objectives were to determine the impact of the patient-clinician relationship on patient adherence to HIV medication, to identify which aspects of the patient-clinician relationship and the treatment system influenced adherence, and to determine which of these variables remained important when the impact of mental distress and substance abuse were considered. The design was a cross-sectional study using a sample of 120 HIV+ clinic patients. The Primary Care Assessment Survey (PCAS) assessed the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 31 publications
2
37
0
Order By: Relevance
“…Similarly, Cooper et al (2004) found that patch use was associated with better treatment participation and cessation outcomes, and that perfect adherence occurred in only one-third of participants. Likewise, adherence problems have been noted among HIV patients in other areas as well (Ingersoll 2004;Ingersoll and Heckman 2005). Smoking interventions should probably contain NRT adherence-enhancing components.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly, Cooper et al (2004) found that patch use was associated with better treatment participation and cessation outcomes, and that perfect adherence occurred in only one-third of participants. Likewise, adherence problems have been noted among HIV patients in other areas as well (Ingersoll 2004;Ingersoll and Heckman 2005). Smoking interventions should probably contain NRT adherence-enhancing components.…”
Section: Discussionmentioning
confidence: 97%
“…A quality patient-provider relationship has also been identified as an important source of support to promote adherence to HIV medication (Ingersoll & Heckman, 2005;Martini, Parazzini, & Agnoletto, 2001;Roberts, 2002) as well as the perception of the provider as open, respectful, empathic and showing genuine interest (Simoni et al, 2003). For example, in a qualitative study of 28 HIV-positive persons, the need for trust in their physicians was commonly identified (Roberts, 2002).…”
Section: Social Factorsmentioning
confidence: 99%
“…The strength of patient-provider relationships is associated with greater patient trust and self-efficacy, and in turn, a higher likelihood of patients' receiving ARV therapy, adhering to ARV regimens, and achieving favorable virologic outcomes. [16][17][18][19][20] Unfortunately, many minority patients face a disadvantage in establishing strong relationships with their providers. Most minorities in the U.S. see providers from racial and ethnic groups different from their own.…”
Section: Introductionmentioning
confidence: 99%